Young People's Experiences of Engaging With Fitspiration on Instagram: Gendered Perspective - Joanne Mayoh; Ian Jones (JMIR Publications, 2021)
BackgroundFitness inspiration or fitspiration is a term used to describe web-based images of fit people, people in the gym, health foods, or inspirational quotes relating to diet and fitness being shared and consumed via visual social media. The popularity of this content is most notable via the Instagram platform. Currently, the majority of fitspiration research has focused on women's experiences; however, increasingly, studies have pointed to the need to explore the gendered ways by which people engage with this content. ObjectiveThe aim of this study is to explore how young men and women engage in fitspiration content on Instagram and provide a gendered analysis of how and why they consume this content. MethodsThis study used a cross-sectional web-based survey (N=1213) of UK-based fitspiration users aged 18-24 years consisting of closed-ended questions to capture quantitative data. ResultsThe majority actively using Instagram for fitspiration (therefore eligible participants) were women (826/1175, 70.30%). Men were more likely to view content posted by athletes (χ21, N=1153=71.8; P=.001) and bodybuilders (χ21, N=1153=32.8; P<.001), whereas women were more likely to view content related to weight loss (χ21, N=1153=36.8; P<.001), diet plans (χ21, N=1153=11.9; P<.001), and celebrities' content (χ21, N=1153=33.5; P<.001). Men were more likely to use fitspiration as a source of inspiration to exercise to gain muscle or get stronger (χ21, N=1147=17.9; P<.001), whereas women were more likely to use fitspiration as inspiration for healthy eating (χ21, N=1147=37.7; P<.001), or to exercise to diet or lose weight (χ21, N=1147=13.5; P<.001). Women were more likely to engage in passive behaviors such as viewing content on their feed (χ21, N=1139=7.9; P=.005) or scrolling through accounts (χ21, N=1139=15.2; P<.001), whereas men were more likely to engage in active consumption by tagging fitspiration accounts in posts (χ21, N=1139=7.2; P=.007), commenting on posts (χ21, N=1139=8.1; P=.004), and posting fitspiration content (χ21, N=1139=6.4; P=.01). ConclusionsFemale fitspiration consumers engaged with content that reinforced the feminine thin but shapely ideal, whereas male users sought out content that reinforced the masculine muscular ideal. Male users were more likely to engage actively with content (eg, posting fitspiration content), while female users were more likely to engage passively (eg, scrolling through accounts, posts, or images). Future research should consider how fitspiration consumption reflects and reproduces oppressive gender ideology.